The changing meanings of objects Calatagan and archaeological research in the Philippines - Tesoro, Grace Barretto (Philippine Studies: Historical and Ethnographic Viewpoints, 2013)
As objects with a biography, artifacts—acquired by individuals or institutions, displayed in museums or privately appreciated—gain different meanings during production, acquisition, deposition in archaeological contexts, recovery, and analysis. This article examines the artifacts recovered from Calatagan, Philippines, to understand the layers and dynamic meanings of objects as commodities, mortuary goods, archaeological data, museum objects, and private collection items. It demonstrates the influence of archaeological practice in the Philippines on the interpretation of the Calatagan sites and artifacts. By understanding how meanings are produced, this article illumines different contexts in which artifacts are utilized and create multiple experiences for people.